Update on diagnosis, pathogenesis and management of ketosis-prone Type 2 diabetes mellitus. (November 2011) - Smiley, Dawn; Chandra, Prakash; Umpierrez, Guillermo E
SUMMARY  Diabetic ketoacidosis (DKA) has been considered a key clinical feature of Type 1 diabetes mellitus; however, increasing evidence indicates that DKA is also a common feature of Type 2 diabetes (T2DM). Many cases of DKA develop under stressful conditions such as trauma or infection but an increasing number of cases without precipitating cause have been reported in children and adults with T2DM. Such patients present with severe hyperglycemia and ketosis as in Type 1 diabetes mellitus but can discontinue insulin after a few months and maintain acceptable glycemic control on diet or oral agents. This subtype of diabetes has been referred to as ketosis-prone T2DM. In this article, we reviewed the literature on ketosis-prone T2DM and summarized the epidemiology, putative pathophysiology and approaches to management.